2013
DOI: 10.12809/hkmj133807
|View full text |Cite
|
Sign up to set email alerts
|

Dysmenorrhoea among Hong Kong university students: prevalence, impact, and management

Abstract: Objective To evaluate the prevalence of dysmenorrhoea, its impact, and management approaches in Hong Kong university students, and to compare between medical and non-medical students for any potential differences in coping strategies.Design Cross-sectional questionnaire survey.Setting The University of Hong Kong, Hong Kong.Participants A total of 240 undergraduate (128 medical and 112 non-medical) students.Main outcome measures Data on the presence and severity of dysmenorrhoea, its impact on daily life, manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
103
4
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 12 publications
17
103
4
9
Order By: Relevance
“…The Chisquare analysis also showed that dysmenorrhea is responsible for significant absenteeism from class (X 2 =15; df=2; p=0.001), loss of concentration (X 2 =12.85; df=2; p=0.02), lack of focus on exam (X 2 =7.4; df=2; p=0.025). Different studies agree with our study findings [9,[12][13][14]17,18,[21][22][23][24]. The negative effect of dysmenorrhea comes at its peak when it brings about missed exams and absenteeism.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The Chisquare analysis also showed that dysmenorrhea is responsible for significant absenteeism from class (X 2 =15; df=2; p=0.001), loss of concentration (X 2 =12.85; df=2; p=0.02), lack of focus on exam (X 2 =7.4; df=2; p=0.025). Different studies agree with our study findings [9,[12][13][14]17,18,[21][22][23][24]. The negative effect of dysmenorrhea comes at its peak when it brings about missed exams and absenteeism.…”
Section: Discussionsupporting
confidence: 87%
“…This figure is relatively higher than prevalence reported by Shah et al [10], Yasir et al [18] and Pejcic et al [20]. In contrasts, the prevalence was relatively lower in studies conducted by Teshome et al [8], El-Hameed et al [11], Mohamed et al [13], Chia et al [14], Khodakarami et al [15], Habibi et al [16] and Sidi et al [17]. The possible reasons for the discrepancy among the estimates could be the difference in the life style of study subjects, the difference in use of selected age group, difference in perception of pain during menstruation, the absence of universally accepted technique of defining dysmenorrhea, a probable disparity in the methods of data collection, study definitions of dysmenorrhea and pain.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…destacam-se os contraceptivos orais, antiinflamatórios não esteroidais e analgésicos que agem reduzindo a dor e/ou o nível de prostaglandinas 11 . A terapêutica mais prevalentemente escolhida pelas mulheres que sofrem com a dismenorreia é o tratamento farmacológico, sendo muitas vezes auto administrado e, portanto, sem intervenção médica nessa escolha 12 . Em um estudo transversal com 197 participantes sobre as estratégias de auto cuidado de mulheres com dismenorreia, as principais…”
unclassified